Untargeted lipidomics and metagenomics reveal the mechanism of aspirin eugenol ester relieving hyperlipidemia in ApoE−/− mice - Lu, Xiao-Rong; Liu, Xi-Wang; Li, Shi-Hong; Qin, Zhe; Bai, Li-Xia; Ge, Wen-Bo; Li, Jian-Yong; Yang, Ya-Jun (Frontiers in Nutrition, 2022)
Hyperlipidemia is induced by abnormal lipid metabolism, which can cause the occurrence of cardiovascular diseases and lead to grievous injury to health. Studies showed that AEE had a significant therapeutic effect on hyperlipidemia and is likely to be associated with the up-regulation of CYP7A1, the key enzyme for cholesterol conversion to bile acids, but no research confirmed whether the effect of AEE on hyperlipidemia was related to the gut microbiota and liver lipids. At the same time, more and more studies have shown that gut microbiota and lipids are closely related to hyperlipidemia. Hence, in this study, we investigated the effects of AEE on liver lipids through LC-MS-based untargeted lipidomics and the effects of AEE on gut microbiota based on cecal contents metagenomics by Illumina sequencing in HFD-induced hyperlipidemia ApoE-/- mice at the overall level. The results of lipidomics showed that AEE relieved hyperlipidemia by decreasing the concentration of 10 PEs and 12 SMs in the liver and regulating the pathways of glycerophospholipid metabolic pathway, sphingolipid signaling pathway, and NF-kappa B signaling pathway. The results of metagenomics concluded that AEE treatment changed the composition of gut microbiota and regulated the functions of lipid transport and metabolism, as well as the metabolism of bile acids and secondary bile acids. The results of the joint analysis between lipidomics and metagenomics showed that the abundance of Verrucomicrobia, Verrucomicrobiales, Candidatus_Gastranaerophilales and Candidatus_Melainabacteria was significantly positively correlated with the concentration of SM (d18꞉1/18꞉0) and PE (16꞉0/18꞉1) in the process of AEE alleviating hyperlipidemia in mice. In conclusion, these results suggested that the effect of AEE on hyperlipidemia was closely related to the gut microbiota by the change of bile acids and liver lipids.